Responses to the Sb epitope contributed to antigenic drift of the influenza A 2009 H1N1 virus: Antigenic drift of the influenza A 2009 H1N1 virus - Ketklao, S.; Boonarkart, C.; Phakaratsakul, S.; Auewarakul, P.; Suptawiwat, Ornpreya (Archives of virology, 2020)
Immunodominance is recognized as a key factor in the antigenic drift of seasonal influenza viruses. In the immunodominance model, each individual in a population predominantly responds to a single epitope among the five antigenic epitopes of the viral hemagglutinin (HA), driving escape mutations one at a time, and sequential mutations in multiple individuals who respond to different epitopes eventually generate a drifted strain with mutations in epitopes that are targeted by a majority of the population. A focused antibody response to the Sa epitope in people born between 1965 and 1979 was believed to contribute to a mutation at HA residue 163 and the first antigenic drift of the 2009 pandemic influenza A H1N1 virus. A serine-to-threonine mutation at HA residue 185 in the Sb epitope emerged in 2010 even before the 163 mutation. We show here that a large fraction of the population in 2010-2011 had responses to the Sb epitope, as shown by 47% of tested sera having altered titers to the S185T mutant. Responses to the Sb epitope showed an age-specific trend similar to that found for the response to Sa epitope in these subjects. Together, the focused responses to Sa and Sb epitopes may have driven the first antigenic drift of the 2009 pandemic H1N1 virus.